2015
DOI: 10.1093/brain/awv066
|View full text |Cite
|
Sign up to set email alerts
|

Roles of microglia in brain development, tissue maintenance and repair

Abstract: The emerging roles of microglia are currently being investigated in the healthy and diseased brain with a growing interest in their diverse functions. In recent years, it has been demonstrated that microglia are not only immunocentric, but also neurobiological and can impact neural development and the maintenance of neuronal cell function in both healthy and pathological contexts. In the disease context, there is widespread consensus that microglia are dynamic cells with a potential to contribute to both centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
249
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 316 publications
(263 citation statements)
references
References 274 publications
3
249
1
1
Order By: Relevance
“…The cellular response to stroke, particularly the response of immune cells, has been studied extensively and has been recently reviewed in detail [19,75]. Post-ischemic inflammation is characterized by an orderly sequence of events involving the brain, its vessels, the circulating blood, and lymphoid organs [19].…”
Section: Cellular Mediators Of Ipcmentioning
confidence: 99%
See 2 more Smart Citations
“…The cellular response to stroke, particularly the response of immune cells, has been studied extensively and has been recently reviewed in detail [19,75]. Post-ischemic inflammation is characterized by an orderly sequence of events involving the brain, its vessels, the circulating blood, and lymphoid organs [19].…”
Section: Cellular Mediators Of Ipcmentioning
confidence: 99%
“…Insulin-like growth factor 1 and VEGF contribute to postischemic neuronal sprouting and angiogenesis, respectively. Stroke also induces profound changes in the systemic immune response [75]. Within a few hours of the onset of cerebral ischemia, brain-immune system interactions can result in downregulation of systemic immunity, a phenomenon known as stroke-induced immunodepression [76].…”
Section: Cellular Mediators Of Ipcmentioning
confidence: 99%
See 1 more Smart Citation
“…31) On the other hand, it should be noted that both neutrophils and microglia/macrophages can be either destructive or protective to injured tissues, presumably depending on their polarized phenotypes. 32,33) These cell populations may act in distinct temporal and spatial patterns to affect the integrity of axonal tracts after ICH insults, and our current working hypothesis is depicted in Fig. 3.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 98%
“…Microglia are CNS-resident immune cells derived from yolk sac macrophages that enter the CNS during early development and maintain themselves as a distinct population from circulating macrophages/monocytes [78][79][80], despite a high overlap in shared expression of many immunohistochemical markers [17,81]. Microglia contribute to the maintenance of brain homeostasis, suggesting a critical role for microglia in the normal physiology of the CNS [56], and pathway analysis of baseline microglial gene expression (from naïve wild-type mouse brain) revealed that the functions most associated with microglia were related to nervous system development [82].…”
Section: Microgliamentioning
confidence: 99%